Harnessing Quality Function Deployment And The House Of Quality Principle For Malaysia’s Dry Ports - Himawan, Abdurrahman Faris Indriya; Sidik, Mohamad Hazeem Sidik; Razik, Muhammad Ashlyzan; Hasan, Md Zaki Muhamad; Wijayantini, Bayu (Eduvest - Journal of Universal Studies, 2023)
The research on dry bulk terminal improvement is currently limited and lacks focus, despite the increasing global demand for dry bulk cargo. The primary aim of this paper is to propose a design for enhancing dry bulk terminal operations and identify a significant factor for improving dry bulk terminal performance through the utilization of the Quality Function Deployment (QFD) method. The fundamental concern in QFD pertains to determining the customer’s desires and formulating an effective strategy to address the identified challenges. These two elements are of utmost importance and are considered essential components within the House of Quality (HOQ) matrices. This study employed systematic procedures that utilized inferential statistics, specifically factor analysis and Spearman correlation, within the context of QFD method. Factor analysis is employed in the process of identifying and selecting the optimal set of unutilized items. The Spearman correlation coefficient was employed to examine and enhance the association between the elements. The findings indicate that there exist significant variables and items that contribute to the enhancement of dry bulk terminal. A study revealed that there exists a moderate and statistically significant correlation between loading time and both labor and machine factors. Additionally, the analysis reveals a substantial correlation between the provision of quality services and the size of the berth. Finally, the analysis reveals a moderate correlation between vehicle control and the operation of lorries. The strategy proposed in this study can be employed by port management to effectively identify solutions in the context of dry bulk terminals.